Education System in Malaysia and Indonesia for Human Resource Development - Othman, Ikhsan (European Journal of Social Science Education and Research, 2017)
Malaysia and Indonesia are implementing their own education system in developing their human resources for nation development. This paper discusses the systems in the countries limited to the main framework of education namely the philosophy of education; curriculum and its implementation; and assessment of students learning. From the philosophy of education point of view, divinity is the underlying aspect of education in Malaysia as well as in Indonesia, with students as the subject of education. Students of today are future human capital for the nation. Therefore education is necessary to develop students' natural potential to produce individuals who are intellectually, spiritually, emotionally and physically balanced and harmonious in line with the purpose of the human existence as inheritors of the earth. From the curriculum point of view, both countries are implementing a standard curriculum which is integrated and dynamic parallel with current needs and global challenges. The content of the curriculum includes knowledges, skills and values with innovations from time to time dynamically. From the aspect of students' learning, the quality of process and the quality of learning outcomes are based on competencies. The assessment of learning does not just focus to final examination results but also ensures the quality of students’ learning process. Generally, it is undeniable that there are some similarities between the two countries in developing their human resources through education. On a positive note, the similarities should be viewed in terms of the benefit to both countries. As the global challenges keep on changing, one day it might become ideas to have mutual collaborations between the two countries in generating higher quality of human resources through education.
Keywords: Education system, human resource development